Variation of water bodies along highways in the Qinghai–Tibet Plateau over the past 20 years: A case study of G109 and G219. Issue 10 (29th September 2022) - Gao, Yu; Chai, Mingtang; Ma, Wei; Li, Yangyang; Chen, Weidong; Mu, Yanhu
Abstract: The water bodies existing along highways in the high altitude areas of the Qinghai–Tibet Plateau (QTP) will aggravate subgrade settlement and road damage, and affect the long-term stability of road networks. Based on remote sensing and geographic information system (GIS) techniques, this study analyzed the changes in the number and area of water bodies along the G109 and G219 highways in the QTP in the past 20 years. The results showed that between 2000 and 2019, the number of water bodies along the two highways increased by 24 and 19%, respectively, and their area increased by 26 and 19%, respectively. The area and the number of water bodies >1 km 2 in the permafrost area and those <1 km 2 in the seasonal permafrost area both changed significantly. The change in the number of water bodies in the permafrost area was positively correlated with annual average temperature, while that in the seasonal permafrost area was significantly positively correlated with annual precipitation. This study provided basic data that could be used in studies on the interrelationship between engineering and water bodies within the context of climate change and will contribute to revealing the mechanisms through which engineering projects affect frozen soils. HIGHLIGHTS: Variation of water bodies along the G219 and G109 highways in China was studied with the consideration of climate change. Characteristics of variation in the number and area of water bodies along G219 and G109 were quantitatively revealed from 2000 to 2019. Difference of correlation between the variation of water bodies and meteorology factors (air temperature and precipitation) in seasonally frozen soil and permafrost regions was examined. Graphical Abstract